Seeded fibrils of the germline variant of human λ-III immunoglobulin light chain FOR005 have a similar core as patient fibrils with reduced stability - Pradhan, Tejaswini; Annamalai, Karthikeyan; Sarkar, Riddhiman; Huhn, Stefanie; Hegenbart, Ute; Schönland, Stefan; Fändrich, Marcus; Reif, Bernd (The journal of biological chemistry, 2020)
Systemic antibody light chains (AL) amyloidosis is characterized by deposition of amyloid fibrils derived from a particular antibody light chain. Cardiac involvement is a major risk factor for mortality. Using MAS solid-state NMR, we studied the fibril structure of a recombinant light chain fragment corresponding to the fibril protein from patient FOR005, together with fibrils formed by protein sequence variants that are derived from the closest germline (GL) sequence. Both analyzed fibril structures were seeded with ex-vivo amyloid fibrils purified from the explanted heart of this patient. We find that residues 11-42 and 69-102 adopt β-sheet conformation in patient protein fibrils. We identify arginine-49 as a key residue that forms a salt bridge to aspartate-25 in the patient protein fibril structure. In the germline sequence, this residue is replaced by a glycine. Fibrils from the GL protein and from the patient protein harboring the single point mutation R49G can be both heterologously seeded using patient ex-vivo fibrils. Seeded R49G fibrils show an increased heterogeneity in the C-terminal residues 80-102, which is reflected by the disappearance of all resonances of these residues. By contrast, residues 11-42 and 69-77, which are visible in the MAS solid-state NMR spectra, show 13Cα chemical shifts that are highly like patient fibrils. The mutation R49G thus induces a conformational heterogeneity at the C terminus in the fibril state, whereas the overall fibril topology is retained. These findings imply that patient mutations in FOR005 can stabilize the fibril structure.
Gesehen am 04.02.2021